Characterization of a Dopamine Transporter and Its Splice Variant Reveals Novel Features of Dopaminergic Regulation in the Honey Bee - Zhang, Vicky; Kucharski, Robert; Landers, Courtney; Richards, Sashika N.; Bröer, Stefan; Martin, Rowena E.; Maleszka, Ryszard (Frontiers in Physiology, 2019)
Dopamine is an important neuromodulator involved in reward-processing, movement control, motivational responses, and other aspects of behaviour in most animals. In honey bees (Apis mellifera), the dopaminergic system has been implicated in an elaborate pheromonal communication network between individuals and in the differentiation of females into reproductive (queen) and sterile (worker) castes. Here we have identified and characterised a honey bee dopamine transporter (AmDAT) and a splice variant lacking exon 3 (AmDATdelta-ex3). Both transcripts are present in the adult brain and antennae as well as at lower levels within larvae and ovaries. When expressed separately in the Xenopus oocyte system, AmDAT localises to the oocyte surface whereas the splice variant is retained at an internal membrane. Oocytes expressing AmDAT exhibit a 12-fold increase in the uptake of [3H]dopamine relative to non-injected oocytes, whereas the AmDATdelta-ex3-expressing oocytes show no change in [3H]dopamine transport. Electrophysiological measurements of AmDAT activity revealed it to be a high-affinity, low-capacity transporter of dopamine. The transporter also recognises noradrenaline as a major substrate and tyramine as a minor substrate, but does not transport octopamine, L-Dopa, or serotonin. Dopamine transport via AmDAT is inhibited by cocaine in a reversible manner, but is unaffected by octopamine. Co-expression of AmDAT and AmDATdelta-ex3 in oocytes results in a substantial reduction in AmDAT-mediated transport, which was also detected as a significant decrease in the level of AmDAT protein. This down-regulatory effect is not attributable to competition with AmDATdelta-ex3 for ER ribosomes, nor to a general inhibition of the oocyte’s translational machinery. In vivo, the expression of both transcripts shows a high level of inter-individual variability. Gene-focused, ultra-deep amplicon sequencing detected methylation of the amdat locus at ten 5'-C-phosphate-G-3' dinucleotides (CpGs), but only in 5-10% of all reads in whole brains or antennae. These observations, together with the localization of the amdat transcript to a few clusters of dopaminergic neurons, imply that amdat methylation is positively linked to its transcription. Our findings suggest that multiple cellular mechanisms, including gene splicing and epigenomic communication systems, may be adopted to increase the potential of a conserved gene to contribute to lineage-specific behavioural outcomes.